American Politics in the Age of Ignorance: Why Lawmakers Choose Belief over Research - Schultz, D. (Palgrave Macmillan US : Imprint: Palgrave Pivot, 2013)
American Politics in the Age of Ignoranc e looks at ten policy myths and bad ideas that governments and public officials - most often conservatives - consistently repeat and re-enact. Acting on these myths, the policies inevitably fail and thereby reinforce preconceived beliefs that government is ineffective at solving problems.